2015
DOI: 10.1086/679015
|View full text |Cite
|
Sign up to set email alerts
|

A round-trip ticket: the importance of release processes for in-stream nutrient spiraling

Abstract: Most nutrient-spiraling studies have focused on estimates of gross uptake (U gross ), which show that streams take up dissolved inorganic nutrients very efficiently. However, studies based on estimates of net uptake (U net ) emphasize that streams tend to be at biogeochemical steady state (i.e., U net ≈ 0), at least on a time scale of hours. These findings suggest that streams can be highly reactive ecosystems but remain at short-term biogeochemical steady state if U gross is counterbalanced by release (R), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 32 publications
5
24
0
Order By: Relevance
“…These discrepancies could be partially explained by the fact that some of these manipulative experiments used monomeric carbohydrates that are easily bioavailable. Moreover, and as previously reported for nutrients, differences between estimates of in-stream gross and net uptake suggest that DOM consumption and production likely occur simultaneously within 25 the stream, and that the former is counterbalanced to some extend by the latter (von Schiller et al, 2015). Supporting this idea, median values of UDOC were >100 fold lower than DOC consumption inferred from measurements of ecosystem respiration calculated from diel cycles of dissolved oxygen concentrations in the same study stream (Lupon et al, 2016b).…”
Section: Empirical Evidence Of In-stream Dom Processingsupporting
confidence: 78%
“…These discrepancies could be partially explained by the fact that some of these manipulative experiments used monomeric carbohydrates that are easily bioavailable. Moreover, and as previously reported for nutrients, differences between estimates of in-stream gross and net uptake suggest that DOM consumption and production likely occur simultaneously within 25 the stream, and that the former is counterbalanced to some extend by the latter (von Schiller et al, 2015). Supporting this idea, median values of UDOC were >100 fold lower than DOC consumption inferred from measurements of ecosystem respiration calculated from diel cycles of dissolved oxygen concentrations in the same study stream (Lupon et al, 2016b).…”
Section: Empirical Evidence Of In-stream Dom Processingsupporting
confidence: 78%
“…Nonetheless, nutrient retention in streams is usually estimated in the space domain from spiraling metrics using combined short‐term additions of a conservative and a reactive solute (Stream Solute Workshop, ; Webster & Valett, ). Noteworthy, this method provides information about gross nutrient uptake, and thus, it can be considered as an estimate of transitory nutrient retention because a fraction of the nutrients retained will be ultimately released to the water column (von Schiller et al, ). Basically, the nutrient spiraling approach allows estimating nutrient uptake rate per unit stream length ( k w , m −1 ), by solving the first‐order equation: Cx=Ctop·()ConxContop·ekwx, where C is nutrient concentration (e.g., NO 3 − , NH 4 + , and SRP) and Con is the ambient conservative tracer concentration (e.g., chloride) at the top of the reach (top) and at the sampling sites located x m downstream during plateau conditions reached by the solute addition.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, nutrient retention in streams is usually estimated in the space domain from spiraling metrics using combined short-term additions of a conservative and a reactive solute (Stream Solute Workshop, 1990;Webster & Valett, 2006). Noteworthy, this method provides information about gross nutrient uptake, and thus, it can be considered as an estimate of transitory nutrient retention because a fraction of the nutrients retained will be ultimately released to the water column (von Schiller et al, 2015). Basically, the nutrient spiraling approach allows estimating nutrient uptake rate per unit stream length (k w , m À1 ), by solving the first-order equation:…”
Section: Nutrient Retention Metricsmentioning
confidence: 99%
“…With a tight and strategically localized sampling methodology, frequent DIN net uptake was detected on a rooted bank and was higher along two subreaches where the root mat was more abundant, suggesting that in this section gross uptake surpassed release processes more consistently (von Schiller et al, ). The lack in FRP net uptake suggested that gross uptake and release processes for this nutrient are consistently in biochemical steady state.…”
Section: Discussionmentioning
confidence: 97%
“…Roberts and Mulholland () therefore suggested that to understand the controls in‐stream features retention processes have on nutrient fluxes and associated export, net uptake was a more useful metric. However, net uptake studies focussing on its triggers and controls under different hydrological, chemical, and biological conditions have remained far less studied, despite increasing interest over its impact on nutrients fluxes (Bernal, Lupon, Ribot, Sabater, & Martí, ; Bernal, von Schiller, Martí, & Sabater, ; Lupon, Martí, Sabater, & Bernal, ; von Schiller, Bernal, & Martí, ; von Schiller, Bernal, Sabater, & Marti, ).…”
Section: Introductionmentioning
confidence: 99%